2022
DOI: 10.3389/fendo.2022.1030278
|View full text |Cite
|
Sign up to set email alerts
|

Combining bioinformatics, network pharmacology and artificial intelligence to predict the mechanism of celastrol in the treatment of type 2 diabetes

Abstract: BackgroundType 2 diabetes (T2D) is a common chronic disease with many serious complications. Celastrol can prevent and treat type 2 diabetes by reversing insulin resistance in a number of ways. However, the specific mechanisms by which celastrol prevents and treats T2D are not well understood. The aim of this study was to explore the key gene targets and potential signaling pathway mechanisms of celastrol for the treatment of T2D.MethodsGSE184050 was downloaded from the Gene Expression Omnibus online database.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In addition, Wu et al. identified HBB as a major player in the iron death signaling pathway in diabetes ( 64 ). Sharma et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Wu et al. identified HBB as a major player in the iron death signaling pathway in diabetes ( 64 ). Sharma et al.…”
Section: Discussionmentioning
confidence: 99%
“…Afridi et al found that HBB polymorphisms upregulated the production of anti-malarial IgG (63). In addition, Wu et al identified HBB as a major player in the iron death signaling pathway in diabetes (64). Sharma et al also found HBB to be enriched in the iron homeostasis and iron death signaling pathways (65).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, AI has made substantial contributions to cancer research and precision medicine (Bhinder et al, 2021). Within the framework of ferroptosis, Wu et al employed a blend of bioinformatics and AI to posit that ferroptosis and the TGF-β signaling pathway potentially underpin the protective attributes of celastrol against type 2 diabetes (Wu and Zhang, 2022). In October 2023, Liu et al demonstrated the potential of deep-learning-assisted phenotypic screening to identify promising lead compounds for alleviating doxorubicin-induced cardiomyopathy by preventing ferroptosis (Liu C. et al, 2023).…”
Section: Emerging Technologies-assisted Tcmmentioning
confidence: 99%
“…The results showed that celastrol (50 μg/kg/d) treatment for 4 weeks could downregulate the expression of P38 protein in the MAPK pathway, reverse the energy remodeling, mitochondrial dysfunction, and oxidative stress induced by STZ-induced SD diabetic rats, thereby delaying the deterioration of heart function and myocardial interstitial fibrosis. The study suggests that the MAPK signaling pathway may be an effective intervention target for DCM ( Wu et al, 2022 ). In another study, celastrol can also alleviate diabetes-induced cardiac damage, inhibit mitochondrial ROS production, and suppress the release of inflammatory factors.…”
Section: Plant Secondary Metabolites-based Diabetes Cardiomyopathy Ta...mentioning
confidence: 99%